2011
DOI: 10.1021/jp108624n
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Catalyst-Assisted Vertical Growth of Dense Carbon Nanotube Forests on Bulk Copper

Abstract: Vertical growth of carbon nanotubes using thermal chemical vapor deposition (CVD) is demonstrated on bulk copper substrates by first sputtering a thin Ni film on the surface of copper. Vertical growth of carbon nanotubes occurred when the nickel film thickness was 20 nm and the carbon nanotubes were grown using a xylene source and additional ferrocene catalyst during CVD. These results show the effectiveness of this method in directly integrating carbon nanotubes with highly conductive substrates for applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…15 In previous studies, we have used Ni thin films on Cu for CVD growth of nanotubes. 16,17 However, in the work presented here, we find that the density and the alignment of the CNTs are superior when using Inconel thin films within a critical thickness range of 10-12 nm.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…15 In previous studies, we have used Ni thin films on Cu for CVD growth of nanotubes. 16,17 However, in the work presented here, we find that the density and the alignment of the CNTs are superior when using Inconel thin films within a critical thickness range of 10-12 nm.…”
Section: Introductionmentioning
confidence: 48%
“…It has previously been shown that ferrocene used without a metal catalyst layer on bare copper does not promote dense nanotube growth either. 9,17 When we heat the Inconel film in the CVD chamber and expose it then to ferrocene alone and no xylene, SEM shows a much greater density of numerous small islands on the surface ͑Fig. 4͒ as opposed to without ferrocene ͓Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The peak has extensively indicated the long range order of perfection or purity in graphitic bonds [12,13,34,35]. The D / G ratios of 1.38 and 0.76 were observed for MWCNTs grown on buffer-free Cu foil and Inconel coated Cu foil as shown in Figures 10(a) and 10(b), respectively.…”
Section: Based On the Sem Images Of Figures 3(b) And 4(b)mentioning
confidence: 92%
“…However, the MWCNTs grown directly on Cu substrates in a large scale production have demonstrated problems due to their low activity with Cu surface [11]. Therefore, the addition of catalysts including Ni, Fe, Co, and their alloys has been necessary [12,13]. For the dense growth of MWCNTs on a metal substrate, the prevention of catalyst diffusion into the oxide layers of the substrate is required.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports suggest that the CNT, graphene and CNT-graphene based hybrid materials are promising for field emission application due to their high aspect ratio, sharp edges and high conductive nature with sp 2 bonded carbon channels, ARTICLE etc. 12 13 Such hybrid material can be grown by different techniques such as chemical vapor deposition (CVD), 7 8 microwave plasma enhanced CVD (MW PECVD), 11 radio frequency plasma enhanced CVD (RF PECVD), 12 sputtering 13 and chemical based methods. 14 CNT and graphene sensors for gas sensing applications are of significant interest due to their tunable electrical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%